TOPICAL LIGNOCAINE TO IMPROVE ORAL INTAKE IN CHILDREN WITH PAINFUL INFECTIOUS MOUTH ULCERS: A BLINDED RANDOMISED PLACEBO-CONTROLLED TRIAL. Issue 10 (7th September 2013) - Hopper, S; Tancharoen, C; McCarthy, M; Lee, K J; Davidson, A; Babl, F
Abstract : Objectives & Background: To establish the efficacy of 2% viscous lignocaine in increasing oral intake in children with painful infectious mouth conditions compared with placebo. Methods: Randomised placebo–controlled trial of viscous lignocaine versus placebo at a single paediatric emergency department. Study staff, clinicians, nurses, care givers, and participants were blinded to the group assignment. Children with acute infectious ulcerative mouth conditions (gingivostomatitis, ulcerative pharyngitis or hand foot and mouth disease), and poor oral fluid intake were randomised to receive 0.15 ml/kg of either 2% viscous lignocaine or placebo with identical appearance and flavor. The primary outcome was the amount of fluid ingested in the 60 minutes following administration of the intervention. Secondary outcomes were specific ml/kg fluid targets and the incidence of adverse events. Results: 100 participants were recruited (50 per treatment group) all of whom completed the 60 minute fluid trial period. Oral intake one hour after drug administration was similar in both groups: lignocaine–mean (standard deviation) 9.48 ml/kg (7.02 ml/kg) vs. placebo 9.32 ml/kg (7.39 ml/kg); mean difference 0.15 ml/kg (95% confidence interval –2.7 ml/kg to 3.0 ml/kg; p=0.9). No evidence for difference between groups was found in secondary outcomes and there were no adverse events in either group. Conclusion: Viscous lignocaine is no better than a flavoured gel placebo in improving oral intake in children with painful infectious mouth ulcers.